FAULT DIAGNOSIS METHOD OF ROTOR SYSTEM WITH SLANT CRACK BASED ON NONLINEAR OUTPUT FREQUENCY RESPONSE FUNCTION - XIA HengHeng; LI ZhiNong; XIAO YaoXian (Jixie qiangdu)
In this paper,the slant crack is used as the object of study,nonlinear output frequency response function（ NOFRF） is introduced to fault diagnosis of rotor system with slant crack. The NOFRF values of slant crack changing with different crack angle and crack location and crack depth are compared,and some valuable conclusions are obtained. The experiment results show that the NOFRF values are very sensitive to different crack angle and different crack location and different crack depth. Therefore,the fault of the slant crack in the rotor system can be effectively monitored according to the change of the NOFRF of the system.